Parenteral Long-Acting Antiseizure Medications Are Used More Often to Treat Seizure Clusters Than Convulsive Status Epilepticus in the Pediatric Emergency Department. (June 2022) - Pfeiffer, Christina K.; Mackay, Mark T.; Long, Elliot; Stephens, David; Dalziel, Stuart R.; Babl, Franz E.; ,
Objective: Recent trials provide high-quality evidence for second-line treatment of convulsive status epilepticus (CSE) in children. However, the most effective medications for other seizure emergencies are poorly understood without established treatment algorithms. We investigated children presenting to the emergency department with repetitive or prolonged convulsions who required intravenous long-acting antiseizure medications, to determine the relative importance and treatment responsiveness of status epilepticus and seizure clusters.Methods: Retrospective observational study in the emergency department, Royal Children's Hospital, Melbourne, Australia (annual census 90 000) using hospital electronic medical records data of patients presenting with seizures in 2018. For patients receiving parenteral long-acting antiseizure medications, seizures were categorized as convulsive status epilepticus, nonconvulsive status epilepticus, and seizure clusters.Results: 1468 patients (2% of all visits) presented with seizures to the emergency department in 2018. Long-acting antiseizure medications were administered to 97 (7%) children for the emergency management of seizures. The majority presented with seizure clusters (n = 69; 71%). Only 11 (11%) were in convulsive status epilepticus and 17 (18%) in nonconvulsive status epilepticus. In convulsive status epilepticus, nonconvulsive status epilepticus, and seizure clusters, phenytoin was used in 27%, 53%, and 58% and levetiracetam in 73%, 47%, and 32%, respectively.Conclusions: Convulsive status epilepticus represents a small portion of patients requiring parenteral long-acting antiseizure medications. Seizure clusters accounted for >6 times the number of convulsive status epilepticus, yet evidence and treatment algorithms are lacking.